2014
DOI: 10.3390/ijms150610738
|View full text |Cite
|
Sign up to set email alerts
|

Damage of Neuroblastoma Cell SH-SY5Y Mediated by MPP+ Inhibits Proliferation of T-Cell Leukemia Jurkat by Co-Culture System

Abstract: The adaptive immune system has implications in pathology of Parkinson’s disease (PD). Research data demonstrated that the peripheral CD4+ T-cell population decreased in pathogenesis of PD. The effect of damaged dopaminergic neurons on peripheral T cells of PD is still unknown. In this study, we constructed a neuronal and glial cells co-culture model by using human neuroblastoma cells SH-SY5Y and gliomas cells U87. After the co-culture cells were treated with neurotoxin 1-methyl-4-phenylpyridinium (MPP+) for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Finally, FACS experiments confirmed that mitochondrial dysfunction and apoptosis were increased in 6-OHDA-and MPP+-treated SH-SY5Y cells (Fig. 1E, F), as reported in previous studies (Wang et al 2014;Chen et al 2021;Ganapathy et al 2016). These results indicate that neurodegeneration was induced in 6-OHDA-and MPP+-treated SH-SY5Y cells that simulated PD.…”
Section: Development Of In Vitro Pd Model Of Sh-sy5y Cells Treated Wi...supporting
confidence: 90%
“…Finally, FACS experiments confirmed that mitochondrial dysfunction and apoptosis were increased in 6-OHDA-and MPP+-treated SH-SY5Y cells (Fig. 1E, F), as reported in previous studies (Wang et al 2014;Chen et al 2021;Ganapathy et al 2016). These results indicate that neurodegeneration was induced in 6-OHDA-and MPP+-treated SH-SY5Y cells that simulated PD.…”
Section: Development Of In Vitro Pd Model Of Sh-sy5y Cells Treated Wi...supporting
confidence: 90%
“…Previous reports showed that neural cells injury could enhance peripheral immune T cells’ proliferation and decrease monocytes migration and invasion [ 7 , 8 , 9 , 10 , 11 ]. In order to evaluate the immune effect induced by heavy ion irradiation and to simulate the in situ condition of the brain, neuron-like SH-SY5Y cells and astrocytic glial U87 cells were cultured together as described previously [ 29 ] and then irradiated with carbon ions (1, 2, or 5 Gy). The medium was collected 24 h after irradiation and applied to immune cells (human leukemia monocytic cell line THP-1 and human leukemic T cell line Jurkat).…”
Section: Resultsmentioning
confidence: 99%
“…Toward the goal of assessing long-term immune responses to radiation, we have addressed the effects of heavy ion irradiation-induced neural cell damage on the peripheral immune system, which plays a key role in maintaining and modulating abscopal effects and systemic effects. We previously established an in vitro co-culture system to investigate neurotoxin-mediated regulation of the proliferation of peripheral immune cells [ 29 ]. In the present study, we examined the long-term effects on the peripheral immune system, including the peripheral blood, thymus, and spleen, after neural cell injury caused by carbon ion radiation in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that significant cell death of RA-differentiated cells was observed after 24 hours of exposure to 500 and 1000 μ M MPP + , and there was no apparent increase in the cell death by extending the exposure period to 48 hours [ 22 ]. For undifferentiated cells, studies showed that cell viability decreased to approximately 50% when cells were treated with 500 μ M MPP + for 24 hours [ 7 , 23 , 24 ]. Similarly, we observed significant cell death after 24-hour exposure of RA-differentiated cells as well as of undifferentiated cells to 250, 500, 1000, and 2000 μ M MPP + .…”
Section: Discussionmentioning
confidence: 99%